IMPLEMENTASI PENGEMBANGAN SISTEM LAPORAN BKD (STUDI KASUS BKD ONLINE KOPERTAIS WILAYAH I DKI JAKARTA) - Sulhi, Ahmad (Kopertais Wilayah I DKI Jakarta dan Banten, 2018)
Implementation of BKD Report Software Development (Case Study of BKD Online Kopertais Region I DKI Jakarta). In the era of information technology advancement today, there are almost no institutions or organizations that do not involve information technology in order to improve the quality of management services for these institutions. The BKD (Lecturer Performance Performance) report so far, which is coordinated by Kopertais 1 DKI Jakarta Region has not been fully optimal and efficient, because it is still managed manually. Therefore, in early 2018, the BKD Report for the Jul-Dec Period 2017, Kopertais 1 DKI Jakarta Region implemented BKD Report assessment policy by online. This application was built using PHP programming language and PostgreSQL database with Laravel framework. The implementation of this policy is not only intended to make the BKD Report more organized, optimal and efficient, it is also expected that all PTKIS lecturers under Kopertais 1 DKI Jakarta Region will eventually be able to take advantage of information technology progress in order to develop scientific quality in accordance with their fields of science.